The Evolution Of Cyberterrorism: Perspectives And Progress From The European Union And Association of Southeast Asian Nation - Haekal Al Asyari (Fakultas Hukum Universitas Islam Indonesia, 2022)
Terrorism, which has caused casualties, economic chaos, and even environmental damage, remains a challenge that must be overcome by the state, whether at the national or international levels. It is crystal clear from the initial circumstances that there is no agreed term to define terrorism, while a new terrorism movement has emerged. By infiltrating cyberspace and hacking critical infrastructure systems, cyberterrorism has generated a shared concern and a collective response by the international community. This article examines these recent developments, from the perspective of the two most progressive regional communities; European Union (EU) and Association of Southeast Asian Nations (ASEAN). With no comparative aim, the author shall try to suggest that although there are different approaches and legal frameworks shared by the two organizations, there is a common goal that is desired to counter cyberterrorism. This paper concludes that the approaches taken by the EU and ASEAN have the similar foundation of value in different ways. The EU places more emphasis on harmonization of national regulations that are supported by regulatory frameworks such as mutual legal assistance. Meanwhile, ASEAN prioritizes diplomatic coordination to increase the capacity and resources of member countries through the e-ASEAN process.Key Words: Cyberterrorism; European Union; Association of Southeast Asian NationAbstrakTerorisme yang telah menimbulkan korban jiwa, kekacauan ekonomi, bahkan kerusakan lingkungan, masih menjadi tantangan yang harus dihadapi oleh negara, baik di tingkat nasional maupun internasional. Tantangan tersebut terlihat jelas dari fakta awal bahwasanya belum ada kesepakatan dalam mendefinisikan terorisme, sedangkan pergerakan baru terorisme telah muncul. Dengan cara menyusup ke dunia maya dan meretas sistem infrastruktur penting, cyberterrorism telah menimbulkan keprihatinan bersama dan tanggapan kolektif oleh komunitas internasional. Artikel ini akan mengkaji perkembangan tersebut, dari sudut pandang dua komunitas regional yang paling progresif; European Union (EU) dan Association of Southeast Asian Nation (ASEAN). Dengan tujuan yang tidak didasarkan untuk melakukan sebuah perbandingan, penulis akan mencoba menggagas bahwa meskipun terdapat pendekatan dan kerangka hukum yang berbeda yang dimiliki oleh kedua buah organisasi tersebut, terdapatnya tujuan bersama yang diinginkan untuk mengatasi cyberterrorism. Tulisan ini menyimpulkan bahwasanya pendekatan yang diambil oleh EU dan ASEAN memiliki landasan nilai yang sama dengan cara yang berbeda. EU lebih menekankan kepada harmonisasi peraturan nasional yang di dukung oleh kerangka pengaturan seperti mutual legal assistance. Sedangkan ASEAN lebih memprioritaskan koordinasi yang bersifat diplomatis untuk meningkatkan kapasitas dan sumber daya negara anggota melalui proses e-ASEAN.Kata kata Kunci: Cyberterrorism; European Union; Association of Southeast Asian Nation